“What’s the point of having friends?”: Reformulating Notions of the Meaning of Friends and Friendship among Autistic People - Bertilsdotter Rosqvist, Hanna; Brownlow, Charlotte; O, Lindsay (Disability Studies Quarterly, 2015)
In this paper we discuss the notion of 'autistic friendship'. Drawing on articles published in the Swedish advocacy magazine Empowerment, written for and by autistic people, a thematic analysis explores two interrelated themes: the meaning and performance of friendship in non-autistic (NT) and autistic (AS) worlds and the meaning of space in social interaction and community. Articles published in the magazine frequently discuss autistic only spaces as safe places in which to make friends with other autistic people and also in which to perhaps learn how to manage social interactions with the dominant non-autistic (NT) culture.